EXPLORING NEUROMARKETING TECHNIQUES: A QUANTITATIVE ANALYSIS OF EYE-TRACKING AND EMOTIONAL ADVERTISING ON FMCG SELF-CARE PRODUCT SELECTION IN BENGALURU - Huzaif, Abdul; Supriya P (International Journal of Research -GRANTHAALAYAH, 2025)
In the competitive FMCG market of today, especially in metro cities such as Bengaluru, it has become vital to comprehend what really moves consumer buying behavior. Although price and quality continue to play a role, numerous purchases are indirectly driven by emotional drivers and rapid mental reactions. In addition to these affective factors, visual attention also takes a vital role in which consumers' gaze, duration of their focus, and what attracts their gaze can strongly influence their interest and final decision. Eye-tracking can facilitate the capture of these unconscious viewing habits, enabling one to associate attention with purchasing behavior. This research examines the impact of neuromarketing methods, namely emotional advertising, brand imagery, and eye-tracking, on buying behavior of consumers in purchasing self-care items like soaps, shampoos, and deodorants. The aim of the research was to evaluate consumer knowledge of neuromarketing and determine the influence of emotional and non-rational components on brand choices and impulse purchases. The sample size was consumers in Bengaluru who regularly bought FMCG self-care items. The sampling unit was independent consumers, who were picked by a probability sampling technique with a simple random sampling method. There were 120 respondents involved in the study via a structured online survey questionnaire. In conclusion, the research emphasizes the role of emotional involvement and implicit effects in guiding consumer choices in Bengaluru's FMCG self-care market. Brands that adopt neuromarketing strategies such as emotional narrative and eye-tracking responsibly and openly can find a competitive advantage and establish healthier consumer relations. Nonetheless, consumer awareness building and protection of privacy are vital for long-term trust development in such methods.